Does the Production Approach to Markup Estimation Match a Stylized Fact? - Forsbacka, Tove (The Review of Economics and Statistics, 2026)
Abstract The production approach to markup estimation has recently attracted the attention of scholars and policymakers for its straightforward implementation and limited data requirements. Criticism has also been directed at the approach and validation of the approach is called for. This paper provides a novel empirical assessment of the approach using rich panel data on the complete population of Swedish firms across four sectors (1998-2019). I first estimate the markup of each firm using the production approach. Using two sources of identification, I then show that these estimates match the stylized fact that markups are higher on more concentrated local markets.